Lepus arcticus Ross 1819 - Robert S. Hoffmann (Smithsonian Institution Press, 1993)
Lepus arcticus Ross, 1819. Voy. Discovery, II; ed. 2, App. IV, p. 170. TYPE LOCALITY: "Southeast of Cape Bowen" (Nelson, 1909:61) [Possession Bay, Bylot Island, lat. 73°37'N, Canada]. DISTRIBUTION: Greenland and Canadian arctic islands southward in open tundra to WC shore of Hudson Bay, thence northwestward to the west of Fort Anderson on coast of Arctic Ocean. Isolated populations in tundra of N Quebec and Labrador, and on Newfoundland (Canada). STATUS: Does not appear to be at risk presently (Flux and Angermann, 1990). SYNONYMS: andersoni Nelson, 1934; bangsii Rhoads, 1896; banksicola Manning and Macpherson, 1958; canus Preble, 1902; glacialis Leach, 1819; groenlandicus Rhoads, 1896; hubbardi Handley, 1952; hyperboreus Pedersen, 1930; labradorius Miller, 1899; monstrabilis Nelson, 1934; persimilis Nelson, 1934; porsildi Nelson, 1934. COMMENTS: Formerly included in timidus by Gureev (1964), Angermann (1967), Honacki et al. (1982), and Dixon et al. (1983), but considered distinct by Corbet (1978c), Hall (1981), A. J. Baker et al. (1983), and Flux and Angermann (1990). Angermann (in litt., 1992) considered it "probably conspecific" with timidus. Published as part of Robert S. Hoffmann, 1993, Order Lagomorpha, pp. 807-827 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 815, DOI: 10.5281/zenodo.7353088